Bypassing nearest hospital for more distant neuroscience care in head-injured adults with suspected traumatic brain injury: findings of the head injury transportation straight to neurosurgery (HITS-NS) pilot cluster randomised trial. Issue 10 (5th October 2017) - Lecky, Fiona Elizabeth; Russell, Wanda; McClelland, Graham; Pennington, Elspeth; Fuller, Gordon; Goodacre, Steve; Han, Kyee; Curran, Andrew; Holliman, Damian; Chapman, Nathan; Freeman, Jennifer; Byers, Sonia; et al.
Abstract : Objective: Reconfiguration of trauma services, with direct transport of patients with traumatic brain injury (TBI) to specialist neuroscience centres (SNCs)—bypassing non-specialist acute hospitals (NSAHs), could improve outcomes. However, delays in stabilisation of airway, breathing and circulation (ABC) may worsen outcomes when compared with selective secondary transfer from nearest NSAH to SNC. We conducted a pilot cluster randomised controlled trial to determine the feasibility and plausibility of bypassing suspected patients with TBI —directly into SNCs—producing a measurable effect. Setting: Two English Ambulance Services. Participants: 74 clusters (ambulance stations) were randomised within pairs after matching for important characteristics. Clusters enrolled head-injured adults—injured nearest to an NSAH—with internationally accepted TBI risk factors and stable ABC. We excluded participants attended by Helicopter Emergency Medical Services or who were injured more than 1 hour by road from nearest SNC. Interventions: Intervention cluster participants were transported directly to an SNC bypassing nearest NSAH; control cluster participants were transported to nearest NSAH with selective secondary transfer to SNC. Outcomes: Trial recruitment rate (target n=700 per annum) and percentage with TBI on CT scan (target 80%) were the primary feasibility outcomes. 30-day mortality, 6-month Extended Glasgow Outcome Scale and quality of life were secondary outcomes. Results: 56 ambulance station clusters recruited 293 patients in 12 months. The trial arms were similar in terms of age, conscious level and injury severity. Less than 25% of recruited patients had TBI on CT (n=70) with 7% (n=20) requiring neurosurgery. Complete case analysis showed similar 30-day mortality in the two trial arms (control=8.8 (2.7–14.0)% vs intervention=9.4(2.3–14.0)%). Conclusion: Bypassing patients with suspected TBI to SNCs gives an overtriage (false positive) ratio of 13:1 for neurosurgical intervention and 4:1 for TBI. A measurable effect from a full trial of early neuroscience care following bypass is therefore unlikely. Trial registration number: ISRCTN68087745.